2020
DOI: 10.1111/fog.12510
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of the drivers of Norwegian spring‐spawning herring (Clupea harengus) recruitment

Abstract: Norwegian spring‐spawning herring (NSSH, Clupea harengus) is a key species in the food‐web and for fisheries in the north‐east Atlantic. NSSH has been the focus of many ecological and fisheries studies over decades and several hypotheses have been put forward to explain variations in its recruitment. We conducted an extensive literature review of the processes that have been hypothesized to control recruitment at age‐2 years. From this review, we constructed a conceptual model to represent how these processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 79 publications
0
12
0
1
Order By: Relevance
“…Bottomup factors, such as changes in temperature and shifts in the abundance and type of prey, have been proposed as potential drivers of recruitment variability in these populations (Cardinale et al 2009). Other studies have suggested that cannibalism and predation from other forage fishes (e.g., Atlantic mackerel, Scomber scombrus) can have a large impact on larval survival (Allan et al 2021), but the ultimate consequences for recruitment and the relative contribution of each process is still largely unknown (Corten 2013;Skaret et al 2015;Garcia et al 2020). In general, it is now clear that the set of recruitment drivers is highly context-dependent, varying in time and space within and among populations (e.g., Zimmermann et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bottomup factors, such as changes in temperature and shifts in the abundance and type of prey, have been proposed as potential drivers of recruitment variability in these populations (Cardinale et al 2009). Other studies have suggested that cannibalism and predation from other forage fishes (e.g., Atlantic mackerel, Scomber scombrus) can have a large impact on larval survival (Allan et al 2021), but the ultimate consequences for recruitment and the relative contribution of each process is still largely unknown (Corten 2013;Skaret et al 2015;Garcia et al 2020). In general, it is now clear that the set of recruitment drivers is highly context-dependent, varying in time and space within and among populations (e.g., Zimmermann et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by spurious correlations and third variables, changing dynamics over time due to, e.g., a regime shift, interactions between variables, inconsistencies in data collection over time, or a combination thereof. In marine ecology, previously established links between population dynamics and environmental drivers could often not be reproduced later on, especially for recruitment (Myers 1998), including in NSS herring (Garcia et al 2021;Zimmermann et al 2019). However, the cause for the deterioration of significant correlations has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…It has an extraordinary long history of commercial fishing and scientific data collection, dating back more than a century. Environmental factors govern the large-scale variations of its population dynamics (Dragesund et al 1980;Garcia et al 2021;Trochta et al 2020) and are assumed to cause most of the year-to-year variation in somatic growth (Ottersen and Loeng 2000). Subsequent changes in size-at-age can affect a wide range of traits such as migration potential (Slotte and Fiksen 2000), optimal swimming speed (Ware 1975(Ware , 1978, metabolic rate (Kiørboe et al 1987) and investment in reproduction (Claireaux et al 2021;Engelhard and Heino 2004).…”
mentioning
confidence: 99%
“…The complexity of fish recruitment variability makes it difficult to assemble all factors that determine recruitment (Houde, 1987). Beside the larval drift there are many other factors that may influence NSS herring recruitment (Garcia et al, 2020). It was beyond the scope of this investigation to test all possible controlling factors; we rather focused on an in-depth investigation into one factor that is a major driver.…”
Section: Discussionmentioning
confidence: 99%